Temperature controlled high-throughput magnetic tweezers show striking difference in activation energies of replicating viral RNA-dependent RNA polymerases - Seifert, Mona; van Nies, Pauline; Papini, Flávia S.; Arnold, Jamie J.; Poranen, Minna M.; Cameron, Craig E.; Depken, Martin; Dulin, David (Nucleic Acids Research, 2020)
RNA virus survival depends on efficient viral genome replication, which is performed by the viral RNA dependent RNA polymerase (RdRp). The recent development of high throughput magnetic tweezers has enabled the simultaneous observation of dozens of viral RdRp elongation traces on kilobases long templates, and this has shown that RdRp nucleotide addition kinetics is stochastically interrupted by rare pauses of 1-1000 s duration, of which the short-lived ones (1-10 s) are the temporal signature of a low fidelity catalytic pathway. We present a simple and precise temperature controlled system for magnetic tweezers to characterize the replication kinetics temperature dependence between 25°C and 45°C of RdRps from three RNA viruses, i.e. the double-stranded RNA bacteriophage Φ6, and the positive-sense single-stranded RNA poliovirus (PV) and human rhinovirus C (HRV-C). We found that Φ6 RdRp is largely temperature insensitive, while PV and HRV-C RdRps replication kinetics are activated by temperature. Furthermore, the activation energies we measured for PV RdRp catalytic state corroborate previous estimations from ensemble pre-steady state kinetic studies, further confirming the catalytic origin of the short pauses and their link to temperature independent RdRp fidelity. This work will enable future temperature controlled study of biomolecular complex at the single molecule level.
CRIS-Team Scopus Importer:2020-06-16